Orbito-frontal cortex and thalamus volumes in the patients with obsessive-compulsive disorder before and after cognitive behavioral therapy - Atmaca, Murad; Yildirim, Hanefi; Yilmaz, Seda; Caglar, Neslihan; Mermi, Osman; Korkmaz, Sevda; Turkcapar, Hakan (Sage Publications Inc, 2018)
Background The effect of a variety of treatment modalities including psychopharmacological and cognitive behavioral therapy on the brain volumes and neurochemicals have not been investigated enough in the patients with obsessive-compulsive disorder. Therefore, in the present study, we aimed to investigate the effect of cognitive behavioral therapy on the volumes of the orbito-frontal cortex and thalamus regions which seem to be abnormal in the patients with obsessive-compulsive disorder. We hypothesized that there would be change in the volumes of the orbito-frontal cortex and thalamus. Methods Twelve patients with obsessive-compulsive disorder and same number of healthy controls were included into the study. At the beginning of the study, the volumes of the orbito-frontal cortex and thalamus were compared by using magnetic resonance imaging. In addition, volumes of these regions were measured before and after the cognitive behavioral therapy treatment in the patient group. Results The patients with obsessive-compulsive disorder had greater left and right thalamus volumes and smaller left and right orbito-frontal cortex volumes compared to those of healthy control subjects at the beginning of the study. When we compared baseline volumes of the patients with posttreatment ones, we detected that thalamus volumes significantly decreased throughout the period for both sides and that the orbito-frontal cortex volumes significantly increased throughout the period for only left side. Conclusions In summary, we found that cognitive behavioral therapy might volumetrically affect the key brain regions involved in the neuroanatomy of obsessive-compulsive disorder. However, future studies with larger sample are required.
Keywords: obsessive-compulsive disorder; cognitive behavioral therapy; orbito-frontal cortex; thalamus